Contributions of the basolateral amygdala and nucleus accumbens to sustaining not just initiating cognitive effort - Matthew L. Dixon; Elizabeth Blevins; Carol S. Dweck; Kai Görgen; Brian Knutson (Proceedings of the National Academy of Sciences, 2026)
People must often sustain cognitive effort to achieve important goals. Although current models recognize that subcortical valuation regions are important for initiating such effort, they have not seen them as playing meaningful roles in sustaining effort throughout task performance. Here, we demonstrate that core subcortical valuation regions—the basolateral amygdala (BLA) and nucleus accumbens (NAcc)—contribute to sustaining cognitive effort on a challenging working memory task. First, convergent univariate and multivariate analyses revealed that the BLA and NAcc represented incentive value, cognitive effort demands, or both, during every task period (encoding, maintenance, and probe/response). Second, trial-to-trial fluctuations in BLA/NAcc multivariate value coding predicted both the strength of frontoparietal cortical engagement and behavioral performance. Third, the BLA and NAcc functionally interacted with frontoparietal regions throughout the task, suggesting that they work in a coordinated manner. These findings reveal a continuous and dynamic role for subcortical valuation regions in sustaining cognitive effort.